Factors influencing the adoption of M-Pesa in South Africa. - Singh, Kiren (My University, 2016)
There are a large percentage of unbanked South Africans, namely South Africans who have access to mobile telephones but do not qualify for a bank account. And then there are banked South African’s, who prefer to use mobile banking due to the convenience and added advantages the facility offers. Banking services and the various channels have evolved considerably over the last few years. Mobile Money has been touted as an effective solution and has proved highly successful in other countries: particularly Kenya and Tanzania. However, the South African Mobile Money market is relatively untapped and the service has been unsuccessful to date. Vodacom (Pty) Ltd is a telecommunications company that primarily provides voice and data services in South Africa and other African countries. The Mobile Money service: M-Pesa - is a product of Vodacom and has been explored in this study in an effort to understand the factors that affect user adoption of such technological services. There is a large gap in the research of Mobile Money, specifically in the South African context, with newer, more robust technology adoption models available, that have yet to be investigated. A review of the literature discovered the Unified Technology Acceptance User Technology Model as the best technology adoption model for studying m-banking adoption due to its comprehensive and modern nature. The Unified Technology Acceptance User Technology Model, combined with specific features of technology characteristics such as: ease of use, age and gender, have been tested in a quantitative study. This paper examined the adoption factors influencing the customer’s propensity to use m-banking. The questionnaire (which consisted of 30, 5 point, Likert-scale style questions) was completed by 189 respondents and assessed using descriptive statistics from Qualtrics and SAS. A Gaussian distribution and data analysis was completed, prior to running Factor Analysis, Discriminate Analysis and Linear Regression on the dependent variables of M-Pesa and Mobile Money.
MBA
Keywords: Consumer behavior,Banks and banking,Financial services industry,Mobile communication systemsMobile commerce ,--South Africa